Consequences of Online Shopping Attributes on E-Commerce Customers - Novi Cahayani; Sri Vandayuli Riorini; M. Maythili; Diandra Vizara Santoso (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to analyze the influence of online shopping attributes, namely Information Quality, Privacy, Perceived Security, Product Variety, and Product Delivery on Customer Satisfaction and Customer Loyalty in Indonesian e-commerce. With a quantitative approach, data were collected through a survey of e-commerce users to evaluate the relationship between these attributes and Customer Satisfaction and Customer Loyalty. Sampling was conducted by targeting the population of active e-commerce users in Indonesia, totaling 270 respondents. The results of the analysis show that three of all attributes (Privacy, Perceived Security, and Product Variety) have a significant positive influence on Customer Satisfaction, which in turn increases Customer Loyalty. Good privacy and a high level of security are key factors in creating Customer Satisfaction. In addition, complete and clear Product Variety information has also proven to be important in improving the shopping experience. This article discusses how each attribute can be optimized to increase Customer Satisfaction and Customer Loyalty in the context of intense competition in the e-commerce industry. These findings provide valuable insights for e-commerce managers in designing more effective marketing strategies to increase competitiveness in the market.